2021
DOI: 10.51441/biomedica/5-165
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Inhibin Alpha (INHα) Mutation (769G>A) in Patients with Premature Ovarian Failure in a Local Population

Abstract: Background and Objective: Premature ovarian failure is a worldwide concern effecting 1% of females of reproductive age. The objective of the present study was to analyze the role of inhibin alpha (INHα) gene mutation (769G>A) in patients with premature ovarian failure (POF) in the local population. Methods: This case-control association studywas conducted in Department of Gynecology, Jinnah Hospital and The Children's Hospital and Institute of Child Health from July 2015-July 2016.A total of n = 100 were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Deliveries at home are attended by unskilled healthcare workers and take place in a potentially hazardous setting, which increases the risk of postpartum haemorrhage and infection to family members or traditional birth attendants who assist births without protective equipment [ 8 ]. Studies showed that home delivery has been associated with young maternal age, low educational attainment, residing in a rural area, low socioeconomic status, timing of first ANC services, distance to health care, and pregnancy complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deliveries at home are attended by unskilled healthcare workers and take place in a potentially hazardous setting, which increases the risk of postpartum haemorrhage and infection to family members or traditional birth attendants who assist births without protective equipment [ 8 ]. Studies showed that home delivery has been associated with young maternal age, low educational attainment, residing in a rural area, low socioeconomic status, timing of first ANC services, distance to health care, and pregnancy complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The maternal mortality rate (MMR) in Pakistan is 276 deaths per 100,000 live births 1 . Pakistan is the fifth-largest contributor to maternal mortality, and six per cent of the world's maternal deaths occur in Pakistan 2 .…”
Section: Introductionmentioning
confidence: 99%